2019
DOI: 10.36740/wlek201904127
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Intestinal Bacterial Overgrowth in the Pathogenesis of Hyperlipidemia

Abstract: Introduction: Small intestinal bacterial overgrowth may cause the hyperlipidemia appearance by enterohepatic circulation disturbance which evolves on the background of the early bile acids deconjugation with further endotoxin production and oxidative stress in the liver with hyperproduction of cholesterol and atherogenic lipoproteins. The aim: the determination of prevalence and features of SIBO in a series of patients with hyperlipidemia and in control subjects. Materials and methods: Nineteen patients with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…SIBO may cause hyperlipidemia through enterohepatic circulation disturbance, which evolves against the background of early bile acid deconjugation with further endotoxin production and oxidative stress in the liver, leading to hyperproduction of cholesterol and atherogenic lipoproteins. SIBO was present in 78.9% of patients with hyperlipidemia and 40% of control subjects, and relationships between the H 2 rate and low-density protein, triacylglycerols, and very low-density lipoprotein levels were observed [150].…”
Section: Hyperlipidemiamentioning
confidence: 95%
“…SIBO may cause hyperlipidemia through enterohepatic circulation disturbance, which evolves against the background of early bile acid deconjugation with further endotoxin production and oxidative stress in the liver, leading to hyperproduction of cholesterol and atherogenic lipoproteins. SIBO was present in 78.9% of patients with hyperlipidemia and 40% of control subjects, and relationships between the H 2 rate and low-density protein, triacylglycerols, and very low-density lipoprotein levels were observed [150].…”
Section: Hyperlipidemiamentioning
confidence: 95%
“…Study shows that Enterobacter cloacae B29 is part of the direct cause of obesity, which is the first internationally recognized ‘fat bacteria.’ Recent study indicates the characteristics of the flora associated with obesity, namely the increase in the number of Firmicutes and the reduction of Bacteroides . Similarly, this situation can occur in type 2 diabetes as well . GM may cause obesity by reducing fasting‐induced adipokine factor (Fiaf) expression.…”
Section: Intestinal Dysbacteriosis and Cardiovascular Risk Factorsmentioning
confidence: 96%
“…Similarly, this situation can occur in type 2 diabetes as well. 54,55 Animal study showed 57 that high-fat-fed mice had increased LPS Gram-negative bacteria in the intestine, elevated plasma LPS levels, causing metabolic endotoxemia and obesity and continued subcutaneous injection of LPS in mice also induced the above reaction. CD14…”
Section: Obesity and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…SIBO may cause the hyperlipidemia appearance by enterohepatic circulation disturbance which evolves on the background of the early bile acids deconjugation with further endotoxin production and oxidative stress in the liver with hyperproduction of cholesterol and atherogenic lipoproteins. SIBO was present in 78.9% of patients with hyperlipidemia and 40% in control subjects, and there was a relationship between hydrogen (H2) rate, and low density protein (LDL), triacylglycerols (TG), and very low density lipoprotein (VLDL) [148].…”
Section: Hyperlipidemiamentioning
confidence: 99%